IMPLEMENTASI PROGRAM PEMBINAAN KEMANDIRIAN NARAPIDANA DALAM PERSEPEKTIF HAK ASASI MANUSIA DI LAPAS KELAS II B ARGAMAKMUR - Dayu, Rio Wisnu; Sakti, Budiman; Sutojo, Adi (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study aims to analyze the success of the Prisoner Independence Development Program in Class II B Argamakmur Penitentiary through four main aspects, namely: communication, resources, disposition, and bureaucratic structure. This study uses a qualitative descriptive approach with data collection techniques through observation, in-depth interviews with employees and visitors, and documentation. The results of the study indicate that the success of the program is greatly influenced by the clarity and consistency of information conveyed transparently to prisoners, by the principles of human rights. In terms of resources, the effectiveness of the program is determined by the availability of trained staff, adequate facilities, and clarity of authority. However, cooperation with external parties and socialization related to post-release job opportunities still need improvement. From the aspect of disposition, commitment, honesty, and the application of democratic values, encourage the implementation of training that is in accordance with the interests of prisoners. However, active participation and the quality of training still need to be strengthened. Meanwhile, in terms of bureaucracy, the implementation of Standard Operating Procedures (SOP) and fragmented division of tasks have created a structured and efficient work system. However, obstacles such as limited facilities and a lack of coordination between parties are still obstacles. This finding underlines the importance of continuous improvement in all aspects to ensure that the development program is truly able to optimally support the process of social reintegration of prisoners after they are released.